INVESTIGATION OF HUMORAL IMMUNITY INDICATORS OF THE ORAL CAVITY IN PATIENTS DEPENDING ON THE DEGREE OF GENERALIZED CHRONIC PERIODONTITIS - Marchenko, A.V. (World of Medicine and Biology, 2020)
The purpose of this research was to investigate the level of oral humoral immunity factors in patients depending on the degree of generalized chronic periodontitis. The study involved 60 patients. The material for the study was unstimulated oral fluid. Determination of lysozyme activity was carried out by the nephelometric method of V.G. Dorofeychuk. The level of sIgA in the oral fluid was identified by enzyme-linked immunosorbent assay according to the manufacturer’s instructions. The correlation coefficient (Pearson’s r) was computed to determine if a relationship exists between the levels of sIgA and lysozyme with the degree of generalized chronic periodontitis. It has been established an increase in the level of immune factors in the oral fluid of patients with generalized chronic periodontitis of I degree. A progressive significant decrease in lysozyme and sIgA was observed under conditions of generalized chronic periodontitis development of II and III degree. The lowest level of these indices was recorded in patients with generalized chronic periodontitis of III degree. We have established an inverse correlation between the levels of sIgA and lysozyme in the oral fluid of patients with the degree of generalized chronic periodontitis. Thus, the degree of generalized chronic periodontitis affects the level of humoral immune factors in the oral fluid and has an inverse correlation with them.